Electrically Conductive Photoluminescent Porphyrin Phosphonate Metal–Organic Frameworks. Issue 13 (30th April 2022) - Zorlu, Yunus; Wagner, Lukas; Tholen, Patrik; Ayhan, Mehmet Menaf; Bayraktar, Ceyda; Hanna, Gabriel; Yazaydin, A. Ozgur; Yavuzçetin, Özgür; Yücesan, Gündoğ
Abstract: Herein, the design and synthesis of a highly photoluminescent and electrically conductive metal–organic framework [ZnCu‐ p ‐H6 TPPA]⋅2 [(CH3 )2 NH] (designated as GTUB3), which is constructed using the 5, 10, 15, 20‐tetrakis [ p ‐phenylphosphonic acid] porphyrin ( p ‐H8 TPPA) organic linker, is reported. The bandgap of GTUB3 is measured to be 1.45 and 1.48 eV using diffuse reflectance spectroscopy and photoluminescence (PL) spectroscopy, respectively. The PL decay measurement yields a charge carrier lifetime of 40.6 ns. Impedance and DC measurements yield average electrical conductivities of 0.03 and 4 S m −1, respectively, making GTUB3 a rare example of an electrically conductive 3D metal–organic framework. Thermogravimetric analysis reveals that the organic components of GTUB3 are stable up to 400 °C. Finally, its specific surface area and pore volume are calculated to be 622 m 2 g −1 and 0.43 cm 3 g −1, respectively, using grand canonical Monte Carlo. Owing to its porosity and high electrical conductivity, GTUB3 may be used as a low‐cost electrode material in next generation of supercapacitors, while its low bandgap and high photoluminescence make it a promising material for optoelectronic applications. Abstract : A highly photoluminescent and electrically conductive metal–organic framework [ZnCu‐ p ‐H6 TPPA]⋅2[(CH3 )2 NH] (GTUB3) is reported. The crystal structure depicts its surface area and charge holding space. Owing to its porosity and high electrical conductivity, GTUB3 may be used as a low‐cost electrode material in next generation of supercapacitors, while its low bandgap and high photoluminescence make it a promising material for optoelectronic applications.